Desarrollo de habilidades en niños de 4 a 5 años mediante aprendizaje basado en juego y Montessori - Albuja Quiguire, Mónica Isabel (2025)
This research examines the issue of fostering rudimentary competencies in children from 4 to 5 years of age in early schooling, highlighting the need to adopt techniques that encourage meaningful discoveries. The main objective is to evaluate the effectiveness of learning through play based on Montessori principles as an educational method that fosters the integral growth of youngsters. Taking into account that a systematic approach has been used that encompasses explicit monitoring and the collection of qualitative and numerical information through a variety of leisure-focused tasks within the educational space, which aim to foster curiosity and investigation The main results show that the use of this technique not only helps to acquire cognitive skills, but also fosters social and emotional competencies, encouraging greaterself-orientation and innovation among young programmers, to refine the document by eliminating all references It is emphasized that the Montessori approach, focusing on the child'sinnate curiosity, provides a sufficient platform to cultivate skills beyond rote learning, fostering a comprehensive and lasting education, encouraging a re-evaluation of contemporary teaching standards in the field of academia